To Be Rated or To Be Indexed: Corporate Governance Rating Experience in Borsa Istanbul - Burak Pirgaip; Mehmet Berktay Akyüz (Istanbul Business Research (IBR), 2020)
We aim at answering whether it is more noteworthy for investors to attain or sustain corporate governance goals by examining how the market reacts towards announcements regarding corporate governance ratings (CGR) and corporate governance index (XCORP) including the firms listed in Borsa Istanbul within the sample period of 2007-2018 using a standard event study methodology. We found that, although both announcements produce relatively weak signals, joint announcements made upon XCORP inclusions along with first ever CGR (attainment) have more significance when compared to single announcements of subsequent CGR (sustainment) in the pre-event period. However, we also determined that the impact of subsequent CGR announcements in the post-event period was more profound. Our results revealed that the market anticipates XCORP inclusions whereas subsequent CGR are unexpected. Besides, the weak support for signaling hypothesis was considered to result from the obscuring effects of current legislation and market practices.
Keywords: 650; Corporate governance; corporate governance rating; corporate governance index; abnormal returns; event study